(untitled) (Research, Society and Development, 2020)
Constructions on soft soil deposits are cause for concern due to the high compressibility and low resistance of these soils, and it is necessary to know their geomechanical properties and improvement techniques. In the alternative of soil reinforcement, geosynthetics can be used at the base of the landfill, allowing for increased stability, faster construction and use of steeper slopes. This article presents the geosynthetic design for reinforcement of a soft soil embankment located in Recife, Pernambuco, Brazil. The objective was to carry out the landfill stability analysis without the reinforcement and with the geosynthetic reinforcement, obtaining the respective values of the safety factors, and therefore, verify the efficiency of this material to reinforce the studied area. The instability mechanisms for expelling soft soil from the foundation and generalized rupture involving embankment, reinforcement and foundation soil were considered. A computer program was used to perform the stability analyzes. The safety factor against expulsion from the soft soil and the minimum safety factor were very close, around 1.3. The use of geosynthetics as reinforcement for the case studied proved to be efficient, with a significant increase in the safety factor from 0.98 to 1.32. The safety factor for the combined use of reinforcement geosynthetics and the construction of a shoulder was 2.37, with the highest value of the three landfill stabilization options. The solution adopted in the project will depend on the value of the minimum safety factor determined by the designer. Several factors such as the size of the work, cost and time, as well as the construction logistics can interfere in the choice of the most appropriate solution. This article seeks a better understanding of the topic, and as a result, to design safer and more economical landfills.